Optimization of process parameters for extraction of xanthine oxidase inhibitor (XOI) from lycopersicon esculentum - Jamal, Parveen; Amid, Azura; Bahardin, Rasidi; Azmi, Saiful Mohammad Nizam (IIUM Press, 2011)
Xanthine oxidase (XO) is an enzyme that catalyses the oxidation of hypoxanthine and xanthine to uric acid, Which plays a crucial role in gout. Gout is distinguished by recurring attacks of joint inflammation. It is influenced by a high dietary intake of foods rich in nucleic acid. Our preliminary screening studies have shown that methanolic extract of Lycopersicon esculentum leaves demonstrated the highest inhibition of XO. Thus, it was subjected to optimization of extraction parameters, which include extraction temperature, extraction time, agitation speed and ratio of the solvent to plant matenals. By using Central Composite Design (CCD) for the optimization, various XO inhibitory activities can be monitored. The optimum conditions as stated by further numerical analysis of the responses using Design Expert v.6.0.8 revealed that the maximum XO inhibitory activity is 88.41% at extraction temperature of 30°C, extraction time of 25.15 hour, extraction speed of 25 rpm, and solvent to plant ratio of 10.71 ml/l g.